(untitled) (Jurnal Penelitian, 2017)
This paper aims to describe the implementation of proselytism of corporate social responsibility (CSR) that is conducted by the company as a business entity that manages natural resources and obligates to carry out social responsibility and environmental enterprise. CSR activities are not only philanthropic activities that have no clear direction and achievement, but those can also be expressed as the realization of proselytism programs in the form of community development with the aim to create the quality of life. The concept of proselytism is not only synonymous with tabligh but also encompassing all aspects of human life to create the change towards the best. The main principle in this proselytism activities is to foster awareness and strength in society as the object of proselytism itself with the aim of improving welfare. Proselytism activities of CSR for people who are in the agricultural area as the main commodity of society are implemented through activities; Land lending, business capital strengthening, management and agricultural development, agricultural cultivation training and marketing of agricultural products. The success of proselytism activities of CSR is supported by factors that support activities such as; Resources, communication and organizational structure that affect each other and strengthen one another.